Evaluation of Thiol Disulfide, Ischemia Modified Albumin, and Prolidase Parameters in Patients With Localized Scleroderma - Ayşe Akbaş; Orhan Sen; Fadime Kılınç; Salim Neselioglu; Gülhan Aksoy Saraç; Akın Aktaş (Mattioli1885, 2024)
Introduction: Localized scleroderma is a rare inflammatory skin disease that causes sclerosis in the dermis and subcutaneous tissue. Oxidative stress may play a role in the etiology or be responsible for the chronicity or progression of the disease. Objectives: We aimed to investigate the presence of oxidative stress in patients with localized scleroderma by examining thiol disulfide balance, ischemia-modified albumin (IMA), and prolidase parameters. Methods: Twenty patients over the age of 18, who were diagnosed with localized scleroderma both clinically and histopathologically and 20 control subjects were included in the study. Age, gender, age of disease onset, duration of the disease, and presence of accompanying systemic diseases were questioned and recorded. Lesion type and modified Rodnan and Lossi scores were calculated through dermatological examination. CRP, sedimentation rate, total thiol, native thiol, and disulfide levels indicated by the Erel profile, IMA level, and prolidase levels were measured and compared in both the patient and control groups. Results: Levels of native thiol (p=0.958), total thiol (p=0.979), disulfide (p=0.449), (disulfide/native thiol%) (p=0.368), (disulfide/total thiol%) (p=0.361), (native thiol/total thiol%) (p=0.368), and prolidase (p=0.121) were similar in both patient and control groups. Only IMA was significantly different. No significant relationship was found between the levels of native thiol, total thiol, disulfide, (disulfide/native thiol), (disulfide/total thiol), IMA, prolidase, and Rodnan and Lossi scores. Conclusion: According to the data obtained from this study, we can say that the thiol-disulfide balance is not disrupted and prolidase levels are not affected in localized scleroderma; however, IMA is negatively affected.